Case report: A successful re-challenge report of GLS-010 (Zimberelimab), a novel fully humanized mAb to PD-1, in a case of recurrent endometrial cancer - Chen, Yeshan; Huang, Ai; Yang, Qin; Yu, Jing; Li, Guiling (Frontiers in Immunology, 2022)
With the widespread use of immune checkpoint inhibitors (ICI), there is growing concern about reports of immune-related adverse events (irAE). In clinical practice, patients who experience severe toxicities by ICI-based therapies would require utmost caution in resuming ICI therapy because of the potential risk of serious irAEs caused by the reintroduction of immunotherapy. In this study, we report a case of recurrent endometrial cancer patient with PD-L1 positive as well as dMMR suffering from immunotherapy-associated myocarditis after first-line treatment with ICI combined with a multi-targeted anti-angiogenic agent. After symptomatic treatment, the patient was in complete remission from treatment toxicities. Subsequently, through MDT discussions, we selected a new PD-1 agent, zimberelimab, for rechallenge therapy, and the patient achieved a sustained disease remission without any treatment-related toxicities. To date, the manner and timing of the ICI re-challenge has been a subject of iterative deliberation. We believe that our experience could shed some light on ICI rechallenge therapy, and we look forward to more literatures to refine the ICI rechallenge scenarios.